1, 25‐Dihydroxyvitamin D3 and dietary vitamin D reduce inflammation in mice lacking intestinal epithelial cell Rab11a. Issue 12 (30th June 2021) - Goswami, Sayantani; Flores, Juan; Balasubramanian, Iyshwarya; Bandyopadhyay, Sheila; Joseph, Ivor; Bianchi‐Smak, Jared; Dhawan, Puneet; Mücahit, Derya M.; Yu, Shiyan; Christakos, Sylvia; Gao, Nan
Abstract: A number of studies have examined the effects of 1, 25‐dihydroxyvitamin D3 (1, 25(OH)2 D3 ) on intestinal inflammation driven by immune cells, while little information is currently available about its impact on inflammation caused by intestinal epithelial cell (IEC) defects. Mice lacking IEC‐specific Rab11a a recycling endosome small GTPase resulted in increased epithelial cell production of inflammatory cytokines, notably IL‐6 and early onset of enteritis. To determine whether vitamin D supplementation may benefit hosts with epithelial cell‐originated mucosal inflammation, we evaluated in vivo effects of injected 1, 25(OH)2 D3 or dietary supplement of a high dose of vitamin D on the gut phenotypes of IEC‐specific Rab11a knockout mice ( Rab11a ΔIEC ). 1, 25(OH)2 D3 administered at 25 ng, two doses per mouse, by intraperitoneal injection, reduced inflammatory cytokine production in knockout mice compared to vehicle‐injected mice. Remarkably, feeding mice with dietary vitamin D supplementation at 20, 000 IU/kg spanning fetal and postnatal developmental stages led to improved bodyweights, reduced immune cell infiltration, and decreased inflammatory cytokines. We found that these vitamin D effects were accompanied by decreased NF‐κB (p65) in the knockout intestinal epithelia, reduced tissue‐resident macrophages, and partial restoration of epithelial morphology. Our study suggests that dietary vitamin D supplementation may prevent and limit intestinal inflammation in hosts with high susceptibility to chronic inflammation. Abstract : Feeding Rab11a ΔIEC mice with dietary vitamin D supplementation led to improved bodyweights, reduced immune cell infiltration, and decreased inflammatory cytokines. Our study suggests that dietary vitamin D supplementation may prevent and limit intestinal inflammation in hosts with high susceptibility to chronic inflammation.